Responses of vegetation and soil microbial communities to warming and simulated herbivory in a subarctic heath - Rinnan, Riikka; Stark, Sari; Tolvanen, Anne (Journal of Ecology, 2009)
1. Climate warming increases the cover of deciduous shrubs in arctic ecosystems and herbivory is also known to have a strong influence on the biomass and composition of vegetation. However, research combining herbivory with warming is largely lacking. Our study describes how warming and simulated herbivory affect vegetation, soil nutrient concentrations and soil microbial communities after 10-13 years of exposure. 2. We established a factorial warming and herbivory-simulation experiment at a subarctic tundra heath in Kilpisjarvi, Finland, in 1994. Warming was carried out using the open-top chamber setup of the International Tundra Experiment (ITEX). Wounding of the dominant deciduous dwarf shrub Vaccinium myrtillus L. to simulate herbivory was carried out annually. We measured vegetation cover in 2003 and 2007, soil nutrient concentrations in 2003 and 2006, soil microbial respiration in 2003, and composition and function of soil microbial communities in 2006. 3. Warming increased the cover of V. myrtillus, whereas other plant groups did not show any response. Simulated herbivory of V. myrtillus cancelled out the impact of warming on the species cover, and increased the cover of other dwarf shrubs. 4. The concentrations of NH4+-N, and microbial biomass C and N in the soil were significantly reduced by warming after 10 treatment years but not after 13 treatment years. The reduction in NH4+-N by warming was significant only without simultaneous herbivory treatment, which indicates that simulated herbivory reduced N uptake by vegetation. 5. Soil microbial community composition, based on phospholipid fatty acid (PLFA) analysis, was slightly altered by warming. The activity of cultivable bacterial and fungal communities was significantly increased by warming and the substrate utilization patterns were influenced by warming and herbivory. 6. Synthesis. Our results show that warming increases the cover of V. myrtillus, which seems to enhance the nutrient sink strength of vegetation in the studied ecosystem. However, ...